Culture-independent assessment of the indigenous microbial diversity of Raniganj coal bed methane block, Durgapur - Chawla, Mansi; Lavania, Meeta; Sahu, Nishi; Shekhar, Sudhanshu; Singh, Nimmi; More, Anand; Iyer, Magesh; Kumar, Sanjay; Singh, Komal; Lal, Banwari (Frontiers in Microbiology, 2023)
It is widely acknowledged that conventional mining and extraction techniques have left many parts of the world with depleting coal reserves. A sustainable method for improving the recovery of natural gas from coalbeds involves enhancing the production of biogenic methane in coal mines. By taking a culture-independent approach, the diversity of the microbial community present in the formation water of an Indian reservoir was examined using 16S rRNA gene amplification in order to study the potential of microbial-enhanced coal bed methane (CBM) production from the deep thermogenic wells at a depth of 800-1200 m. Physicochemical characterization of formation water and coal samples was performed with the aim of understanding the in-situ reservoir conditions that are most favorable for microbial CBM production. Microbial community analysis of formation water showed that bacteria were more abundant than archaea. Proteobacteria, Firmicutes, and Bacteroidetes were found as the most prevalent phyla in all the samples. These phyla play a crucial role in providing substrate for the process of methanogenesis by performing fermentative, hydrolytic, and syntrophic functions.Considerable variation in the abundance of microbial genera was observed amongst the selected CBM wells, potentially due to variable local geochemical conditions within the reservoir. The results of our study provide insights into the impact of geochemical factors on microbial distribution within the reservoir. Further, the study demonstrates lab-scale enhancement in methane production through nutrient amendment. It also focuses on understanding the microbial diversity of the Raniganj coalbed methane block using amplicon sequencing and further recognizing the potential of biogenic methane enhancement through microbial stimulation. The findings of the study will help as a reference for better strategization and implementation of onsite microbial stimulation for enhanced biogenic methane production in the future.